Design and Development of MOOCs to Develop Civil Apparatus Competence for the Banten Provincial Government Toward Banten Corporate University - Muhammad Arif Rahman; Subai; Lilik Nur Kholidah; Farooq Ahmed Jam; Mustofa Kamil; Suherman (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
Competency development is important for every employee and should be empowered for them. Competency development through training consists of classical training and non-classical training. One form of non-classical training is independent learning and self-development through online learning, such as Massive Open Online Courses (MOOCs). The purpose of this research is to figure out the learning process either before and after the development of MOOCs and to develop an information system for training and independent learning as one feature of LMS Banten Ceria in the form of a Massive Open Online Course (MOOC) as an online learning platform with the principle of independent learning or self-directed learning in order to support the Corporate University program in the Province of Banten. This research has a mixed-methods design that blends qualitative and quantitative methodologies. The 4D Thiagarajan model is used in this study, along with research and development methodologies. The result show that MOOCs are effective in developing the competencies of the civil apparatus in the Province of Banten. The difference in average between the pre-test and post-test scores is 20 points. The learning process after using MOOCs shows improvements in knowledge and competence.  Hence, the system of online learning will support the BPSDMD Banten Provincial Program as it becomes a corporate university. Keywords: Development MOOCs, Design MOOCs, Civil Apparatus Competence